Obligations Of The Parties In The Settlement Of Construction Services Contract Disputes Through Arbitration In A Legal Protection Approach - Safnul, Dody (Universitas Dharmawangsa, 2023)
Business activities rife in Indonesia, one of which is the construction services business. The implementation of the construction services business is made by the parties with a construction services contract. In the implementation of construction service contracts, sometimes there are construction service disputes between the parties, both providers and users of construction services, which are decided through arbitration, but there are still many arbitration awards that are not in accordance with the principles of Justice, propriety and certainty so that the arbitration award is applied for cancellation of the decision to the court. Therefore, it needs to be studied in this study.